Exploring The Interplay of Stunting and Upper Respiratory Infection in Kronjo Health Center: A Cross-Sectional Study - Christian, David; Dewi Indah Lestari; Celine Cornelia (HM Publisher, 2024)
Background: Stunting, a prevalent form of chronic malnutrition, presents a significant public health challenge globally, particularly in low-income nations like Indonesia. This study investigates the prevalence and interaction of stunting and upper respiratory infections (URIs) among toddlers aged 12-59 months in Kronjo Health Center, a rural health center in West Java. Methods: Employing a cross-sectional design with total sampling, data were collected from October to November 2023. Height measurements were interpreted according to WHO child growth standards, and statistical analysis was performed using the Pearson chi-square 2x2 test. Results: The study involved 146 toddlers, with the majority being female (52.7%) and aged 12-23 months (34.9%). Most mothers had a high school education (39.7%), practiced breastfeeding (67.8%), and participated in basic pediatric immunization programs (61%). Additionally, 15 toddlers (10.3%) had a history of low birth weight, and a significant proportion were exposed to household smoking (n = 122; 83.6%) and lived in crowded households with six or more family members (n = 45; 30.8%). The study revealed a stunting prevalence of 46.6% and a URI prevalence of 63% among toddlers aged 12-59 months in Kronjo Health Center. Statistical analysis indicated a significant association between stunting and URIs (p-value = 0.035). Conclusion: This study highlights a significant association between stunting and URI among toddlers aged 12-59 months in Kronjo Health Center, emphasizing the importance of addressing both conditions in rural health settings.